2004
DOI: 10.1007/s00330-004-2356-7
|View full text |Cite
|
Sign up to set email alerts
|

An unusual cause of hydrocephalus: aqueductal developmental venous anomaly

Abstract: Vascular malformations are infrequent causes of aqueductal stenoses, developmental venous anomaly (DVA) being the rarest among them. DVAs, also known as venous angiomas, are congenital in origin and characterized by dilatation of vessels in the superficial and deep venous system. Although they are usually clinically silent, they can be complicated by hemorrhage, seizures and neurologic deficits. Herein, we report MR imaging findings of a 7-year-old girl whose hydrocephalus was due to an abnormal vein coursing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 12 publications
0
13
0
2
Order By: Relevance
“…The neurological symptoms were caused by mechanical compression in 32.7% of all cases of symptomatic DVAs with hydrocephalus, tinnitus, brainstem deficits, facial hemispasm, and trigeminal neuralgia being the most common presenting symptoms. 4,8,28,30,31,34,44,45 Obstruction of the ventricles has not only been described for DVAs, but also for dilated drainage veins of an AVM. Potential sites for obstruction are at the level of the interventricular foramen (here related to dilated thalamostriate veins) or at the aqueduct (due to a dilated vein of Galen or transparenchymal venous collectors).…”
Section: Mechanical-related Symptomatologymentioning
confidence: 99%
See 1 more Smart Citation
“…The neurological symptoms were caused by mechanical compression in 32.7% of all cases of symptomatic DVAs with hydrocephalus, tinnitus, brainstem deficits, facial hemispasm, and trigeminal neuralgia being the most common presenting symptoms. 4,8,28,30,31,34,44,45 Obstruction of the ventricles has not only been described for DVAs, but also for dilated drainage veins of an AVM. Potential sites for obstruction are at the level of the interventricular foramen (here related to dilated thalamostriate veins) or at the aqueduct (due to a dilated vein of Galen or transparenchymal venous collectors).…”
Section: Mechanical-related Symptomatologymentioning
confidence: 99%
“…Shunting surgery was performed in 3 patients, 27,28 endoscopic third ventriculostomy in 2 (Case 2 and 29 ), whereas 3 patients (28%) were kept under close clinical observation without published surgical treatment. 30,31 Three patients with nerve compression underwent decompressive treatment with excellent results [32][33][34] (Figure 2). For the remaining patients, the treatment was conservative.…”
Section: Mechanicalmentioning
confidence: 99%
“…In our patient the DVA did not reveal haemorrhage, thrombosis and/or parenchymal abnormalities. A more recent investigation reported alterations in up to 65% of DVAs, like regional atrophy, the most frequent (30%), white matter lesions (28%) and dystrophic calcification 19 . In our patient the standard MR study demonstrated an enlarged infratentorial DVA and according to the patient's symptomatology and MR findings, we also performed a detailed study of the cerebellopontine angle (CPA), comprising an axial 3D-TOF sequence for the evaluation of intracranial vessels and 3D-FI-ESTA or CISS (also know as a sequence to free precession of the steady state) for evaluation of the neurovascular relationship, especially at CPA level.…”
Section: Discussionmentioning
confidence: 99%
“…Also, they present normal blood outflow pathways, and any attempt in removing them surgically, can cause venous infarction or edema (Bannur et al, 2002;Blackmore & Mamourian, 1996;Yagmurlu et al, 2005).…”
Section: Managementsmentioning
confidence: 99%